Impacts of nitrogen and zeolite managements on yield and physicochemical properties of rice grain - Qi, Wu; Guimin, Xia; Taotao, Chen; Daocai, Chi; Ye, Jin; Dehuan, Sun (International Journal of Agricultural and Biological Engineering, 2016)
Zeolite (Z) can hold soil water and nutrient to obtain a higher yield on introduction into moist soil. However, the effects of Z and nitrogen (N) managements on rice grain quality is unclear. Therefore, the effects of different amounts of Z (Z0: 0 t/hm2; Z0.9 and Z0.22: 10 t/hm2 in different particle sizes of 0.45-0.9 mm and 0.17-0.22 mm in diameter) and N (N0, N52.5, N105, N157.5: 0 kg/hm2, 52.5 kg/hm2, 105 kg/hm2, 157.5 kg/hm2), and Z (Z0, Z10: 0 t/hm2, 10 t/hm2) and application frequencies of N on rice yield and grain quality were investigated in 2014 and 2015 in Northeast coastal region of China where Z10 was extended to use in large areas. Results showed that both N and Z applications significantly increased the yields of rough rice (RRY), brown rice, milled rice and head rice. However, there was no significant difference between Z0.9 and Z0.22. The chalkiness area, length-width ratio and head rice rate were not influenced by Z and N applications. However, Z application significantly decreased the chalk rate and slightly increased amylose content (AC) but mattered little to taste value (TV) of rice and rice cooking quality. N could significantly increase rice protein content (PC) but lessen the TV and breakdown value; the order of influence degree on rice yield increasing was as follows: CRF2 (third-split fertilization with Z10), CRF1 (basal fertilization one time with Z10), U2 (urea: third-split fertilization without Z) and U1 (basal fertilization one time without Z). Both CRF1 and CRF2 greatly enhanced the RRY. However, CRF1 was recommended for clear decrease in labor and fuel for growers. Compared with treatments of U1 and CRF1, CRF2 and U2 significantly decreased the AC. PC exhibited significant negative relation to TV and greatly determined the rice eating quality and cooking quality.Keywords: rice grain quality, rice yield, nitrogen, zeolite, physicochemical propertyDOI: 10.3965/j.ijabe.20160905.2535Citation: Wu Q, Xia G M, Chen T T, Chi D C, Jin Y, Sun D H. Impacts of nitrogen and zeolite managements on yield and physicochemical properties of rice grain. Int J Agric & Biol Eng, 2016; 9(5): 93－100.